Target tracking in mixed LOS/NLOS environments - Yi, Lili (2015)
In this thesis, we discuss the problem of tracking the geographic position of a moving target in mixed line-of-sight and non-line-of-sight (LOS/NLOS) environments using measurements including time-of-arrival (TOA), angle-of-arrival (AOA) and time-difference-of-arrival (TDOA).